The Role of Social Self-concept in the Relationship between Gender, Sexual Orientation, and Entrepreneurial Intentions - Miles, Jeffrey A.; Naumann, Stefanie E. (Senate Hall, 2021)
Most research on gender and entrepreneurship has found that women tend to express lower levels of entrepreneurial intentions than their male counterparts. However, studies have not been conclusive regarding the mechanism explaining this gender difference. The purpose of our study is to present and empirically test a model that identifies students' social self-concept, defined as perceptions about their abilities and confidence in social situations, as a critical intervening factor in the relationship between gender and entrepreneurship intentions. In a study of university students in the western U.S., we found that having a strong, positive social self-concept acted as a buffer in the relationship between gender and entrepreneurial intentions for heterosexual persons. In contrast, we did not find such a buffer effect for sexual minorities. We discuss how interventions aimed at boosting individuals' interest in entrepreneurship could target minority groups differently than majority groups.
Keywords: social self-concept|entrepreneurial intentions|gender|sexual orientation